Switching of a Magnet by Spin‐Orbit Torque from a Topological Dirac Semimetal. Issue 23 (3rd May 2021) - Ding, Jinjun; Liu, Chuanpu; Kalappattil, Vijaysankar; Zhang, Yuejie; Mosendz, Oleksandr; Erugu, Uppalaiah; Yu, Rui; Tian, Jifa; DeMann, August; Field, Stuart B.; Yang, Xiaofei; Ding, Haifeng; et al.
Abstract: Recent experiments show that topological surface states (TSS) in topological insulators (TI) can be exploited to manipulate magnetic ordering in ferromagnets. In principle, TSS should also exist for other topological materials, but it remains unexplored as to whether such states can also be utilized to manipulate ferromagnets. Herein, current‐induced magnetization switching enabled by TSS in a non‐TI topological material, namely, a topological Dirac semimetal α‐Sn, is reported. The experiments use an α‐Sn/Ag/CoFeB trilayer structure. The magnetization in the CoFeB layer can be switched by a charge current at room temperature, without an external magnetic field. The data show that the switching is driven by the TSS of the α‐Sn layer, rather than spin‐orbit coupling in the bulk of the α‐Sn layer or current‐produced heating. The switching efficiency is as high as in TI systems. This shows that the topological Dirac semimetal α‐Sn is as promising as TI materials in terms of spintronic applications. Abstract : Room‐temperature switching of magnetization in a CoFeB thin film by a spin‐orbit torque from a neighboring topological Dirac semimetal α‐Sn thin film is reported. The α‐Sn film is grown by sputtering on a silicon substrate. The switching is driven mainly by the topological surface states in the α‐Sn. The switching efficiency is comparable to that in topological‐insulator‐based structures.